Ursodeoxycholyl lysophosphatidylethanolamide improves steatosis and inflammation in murine models of nonalcoholic fatty liver disease - Pathil-Warth, Anita; Müller, Jan; Warth, Arne; Chamulitrat, Walee; Stremmel, Wolfgang (Hepatology, 2012)
Hepatic fat accumulation and changes in lipid composition are hallmarks of nonalcoholic fatty liver disease (NAFLD). As an experimental approach for treatment of NAFLD, we synthesized the bile acid-phospholipid conjugate ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE). Previous work demonstrated profound hepatoprotective properties of the conjugate in vitro and in vivo. Here we investigated the effects of UDCA-LPE in two nutritional mouse models of NAFLD. C57BL/6 mice were fed a high-fat diet (HFD) for 28 weeks, resulting in steatosis with hyperlipidemia. In a second model, mice received a methionin-choline-deficient (MCD) diet for up to 11 weeks, which induced advanced nonalcoholic steatohepatitis (NASH). Establishment of liver injury was followed by intraperitoneal injections of 30 mg/kg UDCA-LPE three times a week for different time periods. UDCA-LPE ameliorated both HFD- and MCD-induced increases in alanine aminotransferase (ALT) values near to normalization. As for metabolic parameters, UDCA-LPE reduced elevated serum triglyceride and cholesterol values in HFD mice. Liver histology showed improvement of steatosis in HFD and MCD mice concomitant with reductions in hepatic triglyceride and cholesterol levels. Additionally, the conjugate lowered serum caspase-8 activity in both models and decreased lipid hydroperoxides in MCD mice. Abundance of proinflammatory lysophosphatidylcholine (LPC), which was detectable in both HFD and MCD mice, was reduced by UDCA-LPE. Quantitative reverse transcriptase-polymerase chain reaction qRT-PCR of liver specimens revealed that UDCA-LPE strongly down-regulated inflammatory genes and modified the expression of genes involved in lipid metabolism. Conclusion: The current study demonstrates that UDCA-LPE improves hepatic injury at different stages of NAFLD. By concurrently lowering hepatic lipid overloading as well as susceptibility of hepatocytes toward inflammatory stimuli, the conjugate may be able to ameliorate disease progression. Thus, UDCA-LPE represents a promising compound suitable for the treatment of NAFLD. (HEPATOLOGY 2012 )
First published: 20 December 2011
Gesehen am 27.06.2018